Phonological context as a trigger of voicing change: a study on the production of english /s/ and /z/ in word-final position by brazilians - Zanfra, Mayara Tsuchida (2013)
Dissertação (Mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês, 2013.